Type-Specific Persistence/Clearance Results in Human Papillomavirus Infections in Turkish Women - Sahin, Haci Ozturk; Gurlek, Beril; Demir, Bulent; Silan, Fatma (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: The persistence of high-risk human papillomavirus infections, most of which are known to be transient is of critical importance for the development of precursor lesions and cancer in the cervix. The aim of the present study is to investigate the persistence and clearance of genotype-based human papillomavirus infections and also some cofactors that could be effective in persistence. STUDY DESIGN: Data of 115 patients whose human papillomavirus and genotype detection was made with multiplex Polymerase chain reaction, and capillary electrophoresis were categorized as low-risk human papillomavirus/high risk human papillomavirus and single/multiple human papillomavirus infections, and clearance/persistence data of two years were investigated. RESULTS: While 82 (71.3%) out of 115 patients (mean age 40.1 years) had a single human papillomavirus infection, the remaining had two or more human papillomavirus infections. Of all human papillomavirus infections, 81.5% (128/157) were high risk-human papillomavirus. Clearance rates of human papillomavirus infections during the first two years was 85.4% (134/157), persistence was 14.6% (23/157). The most frequently persisted high risk-human papillomavirus genotypes were 31, 52, 68, 16, and 35, respectively. A statistically significant difference was not found in human papillomavirus persistence with regard to the infection’s being single/multiple or low-ris/high risk. A significant difference was not found between age groups and persistence. CONCLUSIONS: Of human papillomavirus infections, 85.4% are cleared during the first two years while the most frequently persisted high risk-human papillomavirus genotypes were 31, 52, 68, 16, and 35, respectively. Being aware of population-based clearance/persistence results of type-specific infections may specify screening strategies.